Prevalence of diseases in cleractinian Corals of the Southern Caribbean of Costa Rica - Rodríguez Esquivel, Shanttal Valeria (2025)
The Caribbean Sea has been one of the marine regions most affected by diseases in Scleractinian corals. For Costa Rica, knowledge of coral diseases is scarce. Understanding the health status of these ecosystems is key to take effective conservation measures. Therefore, the objective of this study was to determine the diversity and prevalence of diseases in Scleractinian corals in the southern Caribbean of Costa Rica and their possible relationship with coral cover, physicochemical conditions, and marine protection status. Observations were made during September and October 2023, at the sites of Isla Uvita, Cahuita, Punta Cocles, Puerto Viejo, Punta Uva, and Manzanillo. Based on the visual appearance of the lesions found in the colonies we probably found the presence of five infectious coral diseases: White Band Disease, Dark Spot Disease, White Spot Disease, White Plague Disease, and for the first time in the Caribbean of Costa Rica Stony Coral Tissue Loss Disease (SCTLD). The affected coral species were Acropora palmata, Siderastrea siderea, Porites furcata, and Pseudodiploria strigosa. Porites furcata was affected by the White Syndrome, although the specific disease type could not be identified. The most common disease was White Plague. No significant relationship was found between the prevalence of coral diseases against coral cover, marine protected areas (MPA), and physicochemical factors in the locations of this study (p>0.05). It is recommended to conduct continuous water quality analyses in each locality, such as targeted nutrient, temperature, and sedimentation tests, as these physicochemical factors directly and indirectly impact coral health. This is the first report focused solely on coral diseases in the southern Caribbean of Costa Rica. Due to the possibility of having SCTLD on the reef, it is crucial to maintain adequate monitoring in the area.